Sociedade Rural do Paraná: organização e atuação da fração agrária da classe dominante regional - Valentini, Juliana (2014)
This study aims to analyze the organization and performance of the rural class employers in Paraná, through the study of the Rural Association of Londrina - RAL , in the period from 1946 to 1970. Founded amid intense conflicts and disputes over land in the northern state the entity acted effectively in different regional , state and national mobilizations.Through empirical research identified as the RAL has entered its representatives to the state agencies, which defended their interests economically, socially and politically and organized struggles with other entities against social movements . Through their practices RAL mobilized and organized the collective will of the fraction of the class which it represents articulated strengths and interests to face the struggles of the landholders of Porecatu against the land-grabbers, to criminalize organizations of rural workers and built together with other segments of society the support bases to the civil- military coup of 1964